Income Disparity Trends in Northeast China (1990–2023) : A Regional and Temporal Analysis - Ren, Wandi (2025)
The thesis examines the evolution and determinants of income inequality in Northeast China (Liaoning, Jilin, Heilongjiang) over 1990–2023. Building on Kuznets’ inverted- U, the Lewis–Fei–Ranis dual-sector framework, group-decomposable inequality measures (Theil T; Dagum Gini), and endogenous growth with technology diffusion, I develop testable hypotheses and bring them to data. Using provincial annual panel data, I estimate two-way fixed-effects models and address endogeneity via IV-2SLS with one-period lags of core regressors as instruments. Inequality is measured along two dimensions: inter-provincial (Dagum Gini; weighted Gini as robustness) and urban– rural (Theil T; population-weighted coefficient of variation). The results show that higher per-capita GDP, faster urbanization, and a larger tertiary- sector share are associated with wider inter-provincial and urban–rural gaps, whereas greater fiscal expenditure, a higher primary-sector share, and increased education and R&D inputs mitigate inequality. These patterns are robust to alternative measures and sub-periods (1990–2005 vs. 2006–2023), with clear cross-province heterogeneity in marginal effects. Policy implications include aligning regional coordination with province-specific priorities: accelerating services-led upgrading and factor agglomeration in Liaoning; strengthening innovation and talent policies in Jilin; and deepening basic education and fiscal support in Heilongjiang.